Solitary juvenile xanthogranuloma of the brain - Yanez Perez, Wladimir; Acosta, José Leonardo (Revista Argentina de Neurocirugía, 2024)
Background: xanthogranuloma is a rare benign disease predominantly in the pediatric population, where there is proliferation of histiocytes, producing cutaneous manifestations and very rarely affectation of the central nervous system.Objective: to describe the clinical manifestations, imaging findings and surgical procedure regarding a very rare case compatible with this pathology.Case description: an 8-year-old male patient who debuted with seizures secondary to a single tumor lesion in the left temporal lobe with cystic characteristics and choline peaks in resonance spectroscopy.Surgery: craniotomy and microsurgical tumor resection. Subsequent histopathological study where the presence of histiocytes and plasma cells was evident, as well as positivity in immunohistochemistry of LCA, CD138 and CD68, thus diagnosing a solitary cerebral xanthogranuloma, considered an exceptional and rare finding.Conclusion: thorough and complete planning prior to surgical intervention for these brain lesions, as well as the diagnostic/therapeutic surgical procedure and finally the appropriate anatomopathological study are essential to ensure the best results in patients with this type of pathology.
Keywords: Histiocytosis; Pediatric neurosurgery; Cerebral xanthogranuloma; Juvenile xanthogranuloma